Development and Implementation of the AIDA International Registry for Patients With VEXAS Syndrome - Vitale, Antonio; Caggiano, Valeria; Della Casa, Francesca; Hernández-Rodríguez, José; Frassi, Micol; Monti, Sara; Tufan, Abdurrahman; Telesca, Salvatore; Conticini, Edoardo; Ragab, Gaafar; Lopalco, Giuseppe; Almaghlouth, Ibrahim; et al. (Frontiers in Medicine, 2022)
Objective The aim of this paper is to present the AutoInflammatory Disease Alliance (AIDA) international Registry dedicated to Vacuoles, E1 enzyme, X-linked, Autoinflammatory, Somatic (VEXAS) syndrome, describing its design, construction, and modalities of dissemination. Methods This Registry is a clinical, physician-driven, population- and electronic-based instrument designed for the retrospective and prospective collection of real-life data. Data gathering is based on the Research Electronic Data Capture (REDCap) tool and is intended to obtain real-world evidence for daily patients' management. The Registry may potentially communicate with other on-line tools dedicated to VEXAS syndrome, thus enhancing international collaboration and data sharing for research purposes. The Registry is practical enough to be easily modified to meet future needs regarding VEXAS syndrome. Results To date (April 22nd, 2022), 113 Centers from 23 Countries in 4 continents have been involved; 324 users (114 Principal Investigators, 205 Site Investigators, 2 Lead Investigators, and 3 data managers) are currently able to access the registry for data entry (or data sharing) and collection. The Registry includes 4,952 fields organized into 18 instruments designed to fully describe patient's details about demographics, clinical manifestations, symptoms, histologic details about skin and bone marrow biopsies and aspirate, laboratory features, complications, comorbidities, therapies, and healthcare access. Conclusion This international Registry for patients with VEXAS syndrome will allow the achievement of a comprehensive knowledge about this new disease, with the final goal to obtain real-world evidence for daily clinical practice, especially in relation to the comprehension of this disease about the natural history and the possible therapeutic approaches. This Project can be found on https://clinicaltrials.gov NCT05200715.